The Role of Witness and Victim Protection Agency (LPSK) in Assisting Children as Victims of Sexual Violence - Nathalie Cristine Luban Gaol; Dr. R. Rahaditya, S.H., M.H (Journal of Law, Politic and Humanities, 2024)
One such human rights violation is child sexual abuse, which has a major impact on the psychological and social development of the victim. Children who are victims of sexual violence often experience severe trauma that can affect their lives in the future. The increasing number of cases of sexual violence against children in Indonesia makes it necessary for the state and society to provide protection and support to victims. The Witness and Victim Protection Agency (LPSK) is one of the important institutions responsible for protecting witnesses and victims. One of the human rights violations is sexual violence against children, which has a major impact on the psychological and social development of victims. The increasing number of cases of sexual violence against children in Indonesia makes it necessary for the state and society to provide protection and support to victims. The Witness and Victim Protection Agency (LPSK) is one of the important institutions responsible for protecting witnesses and victims. Despite this, LPSK faces many problems when carrying out its duties. These include budgetary issues, human resources, and cooperating with other related institutions. The purpose of this research is to discover the role of LPSK and how effective they are in assisting child victims of sexual violence.